2015
DOI: 10.1371/journal.pone.0115339
|View full text |Cite
|
Sign up to set email alerts
|

A TagSNP in SIRT1 Gene Confers Susceptibility to Myocardial Infarction in a Chinese Han Population

Abstract: SIRT1 exerts protective effects against endothelial cells dysfunction, inflammation and atherosclerosis, indicating an important role on myocardial infarction (MI) pathogenesis. Nonetheless, the effects of SIRT1 variants on MI risk remain poorly understood. Here we aimed to investigate the influence of SIRT1 polymorphisms on individual susceptibility to MI. Genotyping of three tagSNPs (rs7069102, rs3818292 and rs4746720) in SIRT1 gene was performed in a Chinese Han population, consisting of 287 MI cases and 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…There was no statistically significant difference between the MI cases and controls in terms of age. Traditional MI risk factors were prevalent, as we previously reported [3]. In the comparison of lipid profiles, serum triglycerides (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDLC) were higher in the patients than in the controls ( P < 0.001, P = 0.226, P < 0.001, respectively), whereas serum high density lipoprotein cholesterol (HDLC) levels were significantly higher among controls ( P < 0.001).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…There was no statistically significant difference between the MI cases and controls in terms of age. Traditional MI risk factors were prevalent, as we previously reported [3]. In the comparison of lipid profiles, serum triglycerides (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDLC) were higher in the patients than in the controls ( P < 0.001, P = 0.226, P < 0.001, respectively), whereas serum high density lipoprotein cholesterol (HDLC) levels were significantly higher among controls ( P < 0.001).…”
Section: Resultsmentioning
confidence: 75%
“…Increasing evidences have revealed that genetic polymorphisms in candidate genes are associated with the risk of MI [36]. …”
Section: Introductionmentioning
confidence: 99%
“…All study individuals were genetically unrelated Han Chinese. Inclusion and exclusion criteria, diagnosis, and evaluation as well as criteria for CAD, MI, and controls were described previously [ 4 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hypertension was defined if the individual's systolic and/or diastolic blood pressure (DBP) was above 140/90 mmHg [ 29 ]. Diabetes mellitus, dyslipidemia, and smoking were defined as described in our previous study [ 26 ]. This study was approved by the Ethics Committee of the Affiliated Hospital of Guangdong Medical University and the First People's Hospital of Foshan.…”
Section: Methodsmentioning
confidence: 99%
“…In the current obesity/diabetes epidemic caffeine metabolism is possibly defective [18] and effects of caffeine is via Sirt 1/p53 regulated mitochondria biogenesis with caffeine doses related to p53 mediated mitophagy relevant to cellular programmed cell death [17]. Sirt 1 is relevant to mitophagy [17][18][19][20] in myocardial infarction [81][82][83][84][85][86] and hepatic caffeine metabolism now important to endothelial death and interference of the endothelial NO synthase Figure 3) in the plasma and secondary caffeine saturation of cell membranes. Caffeine can be converted to theophylline in cells but beneficial theophylline effects may be sensitive to toxic elevated caffeine levels in cells.…”
Section: Anti-aging Genes and Caffeine Metabolism With Relevance To Nmentioning
confidence: 99%